Research on Modularized Design and Allocation of Infectious Disease Prevention and Control Equipment in China. (15th November 2016) - Zhao, Xin; Wang, Yun-dou; Zhang, Xiao-feng; Gao, Shu-tian; Guo, Li-jun; Sun, Li-na
Abstract: For the prevention and control of newly emergent or sudden infectious diseases, we built an on-site, modularized prevention and control system and tested the equipment by using the clustering analysis method. On the basis of this system, we propose a modular equipment allocation method and 4 applications of this method for different types of infectious disease prevention and control. This will help to improve the efficiency and productivity of anti-epidemic emergency forces and will provide strong technical support for implementing more universal and serialized equipment in China. ( Disaster Med Public Health Preparedness . 2017;11:375–382)